4y-7=2(9-y)

Simple and best practice solution for 4y-7=2(9-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-7=2(9-y) equation:



4y-7=2(9-y)
We move all terms to the left:
4y-7-(2(9-y))=0
We add all the numbers together, and all the variables
4y-(2(-1y+9))-7=0
We calculate terms in parentheses: -(2(-1y+9)), so:
2(-1y+9)
We multiply parentheses
-2y+18
Back to the equation:
-(-2y+18)
We get rid of parentheses
4y+2y-18-7=0
We add all the numbers together, and all the variables
6y-25=0
We move all terms containing y to the left, all other terms to the right
6y=25
y=25/6
y=4+1/6

See similar equations:

| 9(m-3)+3m=3m=7m+43 | | -116=-2x+2(-4x-3) | | -3u+5=-1 | | 164=3(1+7a)+2a | | -3b+7=-15=2b | | 3x²+4x+8=0 | | 0.2(3z-4)=6.4 | | -7z+15=50 | | b-3/16=5/15 | | I-2x-5=-5 | | 3w-7=20 | | 3(s+2)1s=38 | | (4*8y)=8y*8y-2912 | | 28=16x | | (w+2)^2=44 | | 9(x+1)=6x-18 | | (w+2)^2+4=48 | | 12/72x-108/144=13/4 | | w^2+4w-40=0 | | 2y-5=-5 | | 2/3+u=1/4 | | 3(2x+5)-x=-7(x+3) | | 3(2x+5)-x=-7(x+3 | | 190=7x-4(-5x-7) | | 13=-3x+5x+10 | | 2(y-4)=-4(y-8) | | 5/2*x=-5 | | (2/3)k-(k+(1/3))=(1/9)(k+3) | | 10x+8=8x+4 | | 2/3x-(x+(1/3))=1/9(x+3) | | f/5-6=8 | | 600+x=40 |

Equations solver categories